HIV/AIDS-related stigma and its associated prejudice and discrimination - Mphumela, Funeka Jeane (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2009.